Evoked nostalgia, personal continuity and behavioural outcomes: a study of Generation X and Y consumers in a South African context - Heyns, Grethe (Stellenbosch : Stellenbosch University, 2021)
Thesis (MCom)--Stellenbosch University, 2021.